Appraising Feedback Stance in Higher Education: A Corpus-Assisted Discourse Study of Student and Academic Perceptions, Perspectives and Preferences - Poucke, Margo Van (Corpus pragmatics : international journal of corpus linguistics and pragmatics, 2025)
Feedback is a complex dialogic, sociomaterial practice that is shaped by digital affordances, institutional norms and various contextual factors. Even though it is widely recognised as crucial to academic development, student perspectives on the practice of feedback remain underexplored. This study examines appraisal strategies in social media discourse and academic writing by analysing the use of attitude, engagement and graduation markers in over 5,000 posts and comments on r/college and 100 research articles on feedback. Using a mixed-methods approach that combines advanced statistical modelling and qualitative appraisal analysis, the study identifies prominent register-specific patterns. Students’ reflections and comments are predominantly attitude-driven due to the prolific use of attitude markers and upscaling to engage in joint emotion regulation when processing past feedback experiences. This appraisal strategy encourages affiliative alignment and reflects the interactive and affective nature of online discussions. In contrast, academic writing is characterised by engagement-driven variation, with scholars employing contractive and expansive appraisal resources to negotiate disciplinary interpretations. Educational researchers favour entertain, appreciation and focus markers to evaluate conceptualisations and processes of feedback. The findings confirm the emotional impact of critique and reveal students’ preference for clear, empathetic, actionable feedback, while frustration arises from vagueness, unfairness or excessive criticism. Academics view feedback as a structured, discursive process that should be constructive, evidence-based and compliant with disciplinary norms, recommending transparency, justification and cultural responsiveness. Recognising the students’ standpoint and suggestions can inform the co-design of more effective feedback practices that combine emotional responsiveness and goal-oriented guidance for self-development.